Dental caries and related factors in the elderly of the Azar cohort population: A cross-sectional study. - Maryam Hosseinpour Sarmadi; Nasrin Sharififard; Zeinab Mahboobi; Elnaz Faramarzi; Aylin Bilehjani (PLoS ONE)
Objective Oral health is often overlooked among the elderly due to the numerous comorbidities prevalent in this population. However, oral health significantly influences quality of life by affecting both general health and psychological well-being. The present study aimed to assess dental caries in elderly individuals using the DMFT index (decayed, missing, and filled teeth) and to explore its relationship with various factors based on data from the Azar cohort study in Iran. Materials and methods In this cross-sectional study, data from the initial phase of the Azar cohort study, which involved 2629 elderly individuals (aged 60 years and older), were statistically analyzed. The Azar cohort study evaluated demographic factors, the history of chronic diseases, and behavioral habits using a well-designed questionnaire administered through face- to -face interviews. The DMFT index was evaluated through oral examination. A negative binomial regression analysis with a log link function was employed to investigate the relationship between the DMFT and related variables, including gender, age, marital status, level of education, socioeconomic status, chronic diseases, smoking, alcohol consumption, and body mass index. Results The mean (SD) age of elderly individuals was 64.15±2.91 years. The mean (SD) DMFT was 28.42±6, and the mean (SD) number of missing teeth was 26.58±8.36. Approximately 70.8% of elderly individuals were edentulous. Women exhibited a higher mean DMFT score and a greater number of missing teeth compared to men. The mean DMFT score and its components significantly differed based on the level of education and socioeconomic status. However, no significant relationship was found between the DMFT index and the variables in the multiple regression analysis. Conclusion The high prevalence of edentulism and the elevated DMFT scores in the elderly population of the Azar cohort indicate a poor oral health status among older individuals. Providing the dental services within the primary health care system for the adults, can be beneficial in improving oral health in old age.